Protein Engineering of a Germacrene A Synthase From Lactuca sativa and Its Application in High Productivity of Germacrene A in Escherichia coli - Chen, Rong; Liu, Yuheng; Chen, Shu; Wang, Ming; Zhu, Yao; Hu, Tianyuan; Wei, Qiuhui; Yin, Xiaopu; Xie, Tian (Frontiers in Plant Science, 2022)
Germacrene A (GA) is a key intermediate for the synthesis of medicinal active compounds, especially β-elemene which is a broad-spectrum anticancer drug. Production of sufficient GA in microbial platform is vital for the supply precursors of active compounds. In this study, the E. coli BL21 Star (DE3) was used as host and cultivated in SBMSN medium, obtaining a highest yield of FPP precursor. The GAS from Lactuca sativa (LTC2) exhibited the highest levle of GA production. Secondly, two residues involved in product release (T410 and T392) were substituted with Ser and Ala, respectively, responsible for relative higher activities. Next, substitution of selected residues S243 with N caused an increase on activity. Further, T392A-T410S and S243N-T410S were created by combination with the beneficial mutation, and they demonstrated dramatically enhanced titers with 1.90 fold and productivity with 5.44 fold, respectively. Finally, production titer of GA reached 126.4 mg/L and the highest productivity was 7.02 mg/L.h by I364K-T410S mutant in shake-fask batch culture after 18h fermentation. To our knowledge productivity of I364K-T410S mutant is the highest ever reported. This result highlights a promising method for industrial production of GA in E. coli, and lays a foundation for further pathway reconstruction and the biotechnological production of valuable natural sesquiterpene.